Evaluating the feasibility of study methods for a future trial-based economic evaluation of a multistage shared decision-making program for type 2 diabetes mellitus: Protocol for a cluster-randomized controlled pilot study. - Anna Tichler; Dorijn F L Hertroijs; Ghislaine A P G van Mastrigt; Martijn C G J Brouwers; Dirk Ruwaard; Arianne M J Elissen (PLoS ONE)
Introduction We developed a multistage shared decision-making program for type 2 diabetes that aims to support person-centered type 2 diabetes management in primary care. The program consists of an online patient decision aid, a preparatory consult for patients, and interprofessional training for healthcare professionals. The short- and long-term effectiveness of the multistage shared decision-making program needs to be researched in a trial-based economic evaluation. To evaluate the feasibility of study methods for such an evaluation, we will conduct a pilot study. In this article, we outline its protocol, which focuses on sample recruitment and retention, study management, and feasibility of outcome and cost measurements. Methods and analysis The multistage shared decision-making program will be pilot-tested in a cluster-randomized controlled trial in four primary care practices (located in the region of Gorinchem, the Netherlands) using a convergent parallel mixed-methods approach. The intervention practices will adopt the program, whereas the control practices provide usual care. Data collection will include recruitment, retention, and consent rates, patients' sociodemographic and clinical characteristics, and the assessment of primary and secondary outcomes of the future trial-based economic evaluation. We will also collect data on the usage behavior of patients when completing questionnaires of the primary and secondary outcomes (i.e., time needed to complete questionnaires). Semi-structured interviews with patients will be conducted to obtain insights into the understandability and usability of measurement tools. Moreover, focus groups with healthcare professionals from participating practices will be organized to complement the quantitative data on sample representativeness and to assess the study management challenges of participating practices. Discussion The pilot will address uncertainties around the feasibility of a future trial-based economic evaluation, focusing on sample recruitment and retention, study management, and the feasibility of outcome and cost measurements. The results will guide the improvement of study procedures for the economic evaluation of our multistage shared decision-making program for type 2 diabetes. Trial registration The study is registered at ClinicalTrials.gov: NCT06410768.